Rancangan Aplikasi Pengaduan Pelayanan Berbasis Mobile di Perpustakaan Kabupaten Ngawi - Zam Afuw Imama Sugiman; Sri Wulandari (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The Ngawi Regency Library and Archives Office has an obligation to provide public services to people who want to access local government library facilities. In providing services, it is required to provide good service to people who want to access the library. The community has the right to provide an assessment of services such as complaints, criticism, or suggestions. But so far, the library service complaint system is still done manually. The manual method has several weaknesses such as complaints are not recorded, complaint data is not stored, and other human errors. For this reason, researchers made research on a new complaint system to be efficient and overcome problems in the manual system. Researchers designed a mobile-based library service complaint application as a solution from the results of observation and analysis of the previous complaint system. The solution resulted from redesigning the new system design with system design analysis including Flowchart, Unified Modeling Language (UML), table relations, and Black-box testing. With the new system, it is hoped that it can facilitate the community in making complaints about library services through applications installed on smartphones. Assisting library staff in monitoring, processing, and storing complaint data from the community through the library admin website.